Labour law violations in Chile. (December 2013) - KANBUR, Ravi; RONCONI, Lucas; WEDENOJA, Leigh
Abstract: This empirical contribution to the quantification of labour law violation uses micro survey data to examine compliance with workers' statutory entitlements to a minimum wage, working time limits, a written contract, and pension coverage over the period 1990–2009. One‐third of workers were denied at least one of these entitlements, albeit with significant variations in the incidence of violations over time, across laws and by worker and firm characteristics. The authors' econometric analysis shows that compliance rates are lower for female, foreign‐born, indigenous and less educated workers, and in smaller firms and agricultural regions. Further research, they argue, should focus on enforcement.